2022
DOI: 10.1038/s41467-022-32660-y
|View full text |Cite
|
Sign up to set email alerts
|

Codoped porous carbon nanofibres as a potassium metal host for nonaqueous K-ion batteries

Abstract: Potassium metal is an appealing alternative to lithium as an alkali metal anode for future electrochemical energy storage systems. However, the use of potassium metal is hindered by the growth of unfavourable deposition (e.g., dendrites) and volume changes upon cycling. To circumvent these issues, we propose the synthesis and application of nitrogen and zinc codoped porous carbon nanofibres that act as potassium metal hosts. This carbonaceous porous material enables rapid potassium infusion (e.g., < 1 s cm−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(38 citation statements)
references
References 79 publications
1
37
0
Order By: Relevance
“…[40] Except for the presence of CoN x C species in the SA-Co@HC, the N doping configuration of both HC and SA-Co@HC from the N 1s XPS spectra can be deconvoluted into four nitrogen dopants contributions, including pyridinic-N, pyrrolic-N, graphitic-N, and oxidized-N (Figure 2e and Figure S10, Supporting Information). It was reported that the potassiophilic nitrogen functional sites show large binding energy and stronger adsorption ability for K ion, [29,31,41] which is conducive to regulating the K nucleation and growth property. Overall, all these characterizations confirm the ideal design of envisaged structure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[40] Except for the presence of CoN x C species in the SA-Co@HC, the N doping configuration of both HC and SA-Co@HC from the N 1s XPS spectra can be deconvoluted into four nitrogen dopants contributions, including pyridinic-N, pyrrolic-N, graphitic-N, and oxidized-N (Figure 2e and Figure S10, Supporting Information). It was reported that the potassiophilic nitrogen functional sites show large binding energy and stronger adsorption ability for K ion, [29,31,41] which is conducive to regulating the K nucleation and growth property. Overall, all these characterizations confirm the ideal design of envisaged structure.…”
Section: Resultsmentioning
confidence: 99%
“…The nucleation overpotential (µ nuc ) is defined as the difference between the voltage dip at the beginning and the stable mass transfer-controlled potential plateau (µ pla ) afterward. [14,29,42] The initial µ nuc decreased from 150 mV for bare Cu, 5 mV for HC to 3 mV for SA-Co@HC, and the µ pla of the SA-Co@HC is also smaller than that of Cu foil and HC electrode (Figure S13, Supporting Information). This result indicates that the SA-Co@HC as a K host has a lower nucleation energy barrier and faster charge transfer capability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many solutions have been proposed by the modification of the current collector (CC) with better K metal affinity on the underlying substrate 10 and the protection of metal anode with artificial solid electrolyte interphase (SEI) layer on the K metal surface. 11 The CC modifications, such as those of NiO nanoparticle nucleation sites that modified puffed millet, 12 SnO 2 -coated conductive porous carbon nanofiber framework, 13 Cu 3 Pt alloyfunctionalized Cu meshes, 14 amine functionalization of carbon clothes, 15 Co-doped porous carbon nanofibers, 16 and Al powders or graphene-coated Al foils, 10,17 have been reported to improve the potassiophilicity of the underlying substrate. Although these works promote the interfacial contact between K metal and a CC surface, the high reactivity of K metal results in an inefficient plating-stripping process, leading to low Coulombic efficiency (CE) and inferior cyclic performance.…”
Section: Introductionmentioning
confidence: 99%